From Colonialism to Globalisation: How History Has Shaped Unequal Power Relations Between Post-Colonial Countries (Glocalism: Journal of Culture, Politics and Innovation, 2020)
This paper examines the ways globalising initiatives have been used to mirror neo-colonial practices and foster unequal power relationships between countries in the Global North and Global South. By taking a historical perspective, this paper points to the ways inequality is structured over time and highlights how many globalising mechanisms such as the spread of free markets, foreign lending, and the myth of development theory have favoured growing inequalities. To clarify how globalisation creates neo-colonial relations in modernity, two examples shall be used: the Green Revolution in India and the effects of the Newmont mining corporation in Peru.
Keywords: globalisation; colonialism; cultural hegemony; development theory; foreign lending